1997
DOI: 10.1103/physrevb.56.9091
|View full text |Cite
|
Sign up to set email alerts
|

Stripes, pseudogaps, and Van Hove nesting in the three-bandt-Jmodel

Abstract: Slave boson calculations have been carried out in the threeband tJ model for the high-Tc cuprates, with the inclusion of coupling to oxygen breathing mode phonons. Phononinduced Van Hove nesting leads to a phase separation between a hole-doped domain and a (magnetic) domain near half filling, with long-range Coulomb forces limiting the separation to a nanoscopic scale. Strong correlation effects pin the Fermi level close to, but not precisely at the Van Hove singularity (VHS), which can enhance the tendency to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 104 publications
(100 reference statements)
2
40
0
Order By: Relevance
“…We have suggested that other VHS-stabilized phases are more likely 52 (see also Ref. 53), and here we explore the properties of a Class A CDW phase 48 . At a doping x ∼ 0.25, the effects of correlations are relatively weak, renormalizing the bandwidth by a factor of ∼2.…”
Section: F What Stabilizes Charged Stripes?mentioning
confidence: 99%
See 2 more Smart Citations
“…We have suggested that other VHS-stabilized phases are more likely 52 (see also Ref. 53), and here we explore the properties of a Class A CDW phase 48 . At a doping x ∼ 0.25, the effects of correlations are relatively weak, renormalizing the bandwidth by a factor of ∼2.…”
Section: F What Stabilizes Charged Stripes?mentioning
confidence: 99%
“…The two most common interpretations for the pseudogap are in terms of either precursor pairing or a competing order parameter, which may be magnetic 74,75 or charge-density wave (CDW) 48,76 . We will argue in the next subsection that the latter possibility is more likely.…”
Section: Termination Of Stripesmentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal line corresponds to the value of K 0 + K Coul estimated according to formulas (16) and (18) The line corresponding to K η (x c0 ) is obtained using K ηM (x c0 ) given by Eq. (20) with J = 125 meV.…”
Section: Combining the Estimatesmentioning
confidence: 99%
“…Theoretically, the general tendency towards phase separation in cuprates and cuprate-related models is extensively discussed in the literature [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], but any conclusion about the actual presence or absence of phase separation suffers from uncertainties associated with the gross simplifications in the models. The important advantage of the phase separation measure introduced in this work is that it is directly applicable to real materials.…”
Section: Introductionmentioning
confidence: 99%